The influence of plant growth regulators on phytochemical components in the leaves and calyxes of Roselle (Hibiscus sabdariffa L.) - Media I. MuhammedAmin; Sawsan M. S. Ali Kanimarani (Zanco Journal of Pure and Applied Sciences, 2020)
A study was conducted at the open field of Zanco Village, Erbil-Iraq in 2018 to determine the effect of foliar application of some plant growth regulators (IAA, BA and GA3 ) on phytochemical components in the leaves and calyxes of Roselle. The investigation was performed as factorial experiment under randomized complete block design with three replications, growth regulators were foliar applied alone or combined treatments as: control, IAA (100 mg.l-1) , BA (150 mg.l-1), GA3 (150 mg.l-1), IAA (100 mg.l-1) + BA (150 mg.l-1) , IAA (100 mg.l-1) + GA3 (150 mg.l-1), BA (150 mg.l-1)+GA3 (150 mg.l-1) and IAA (100 mg.l-1) + BA (150 mg.l-1) + GA3 (150 mg.l-1). Parameters under study were: Moisture content (%) in the stem and Chlorophyll (spad) (%), Protein (%), Total soluble solid (%), Total flavonoids (mg. g-1), Anthocyanin (mg.kg-1), Ascorbic acid (vitamin C) mg.kg-1, Genistein (mg.kg-1), Hesperetin (mg.kg-1) and Myrecetin (mg.kg-1), were recorded in the leaves and calyxes of Roselle. Results showed that the highest levels of plant growth regulators in single and combined forms give the highest values of the above-mentioned parameters except treatment 100 mg.l-1 IAA caused significant difference only in total flavonoids (mg.g-1).